Explicando os ciclos de negócios (Economia Aplicada, 2000)
This paper describes the recent macroeconomic debate involving basically two schools of thought: new classical and new keynesian. Some of the main research fields related to the topic are described. In doing so, we want to enhance the theories's understanding and placement, in order to provide a first glance at the debate as a whole.